The Relationship Between Interpersonal Communication and Job Satisfaction Among Restaurant Employees in Deli Serdang Regency - Doli Maulana Gama Samudera Lubis (Manunggal Halim Jaya, 2026)
This study aimed to examine the relationship between interpersonal communication and job satisfaction among restaurant employees in Deli Serdang Regency, Indonesia. This study employed a quantitative approach with a correlational research design. The population consisted of 67 restaurant employees, and all members of the population were selected as research participants through a total sampling technique. Data were collected using Likert-scale questionnaires developed based on dimensions of interpersonal communication and job satisfaction. Prior to data collection, the research instruments were tested for validity and reliability to ensure the quality and consistency of the measurement. Data analysis was conducted using Pearson’s product-moment correlation technique with the assistance of statistical software. The findings revealed a significant positive relationship between interpersonal communication and job satisfaction (r = 0.57, p < 0.01). The correlation coefficient indicates that interpersonal communication has a moderately strong association with employee job satisfaction. Furthermore, interpersonal communication contributed 32.49% to the variance in job satisfaction, while the remaining percentage was influenced by factors beyond the scope of this study. These findings suggest that better interpersonal communication among employees and between supervisors and subordinates is associated with higher job satisfaction among restaurant employees. This study highlights the importance of interpersonal communication in fostering a conducive, open, and supportive work environment to enhance employee well-being and work quality, particularly within the restaurant industry, which is characterized by intensive teamwork and social interactions.